2015
DOI: 10.1136/vr.102569
|View full text |Cite|
|
Sign up to set email alerts
|

Sedation and mechanical antinociception after intravenous administration of detomidine in donkeys: a dosage–effect study

Abstract: There is limited, useful, scientific information on detomidine in donkeys. This study compared the effects of intravenous saline, detomidine (10, 13.5, 17 and 20 μg/kg) and acepromazine (50 μg/kg) in donkeys by computing areas under the curve for 0-30, 30-60 and 60-120 minutes (AUC0-30, AUC30-60 and AUC60-120) for sedation scores, head heights and mechanical nociceptive thresholds (MNTs). For sedation scores, all detomidine treatments, except 10 μg/kg, increased AUC0-30 values compared with saline, and AUC0-30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Donkeys receiving the higher dose of xylazine showed HHAG values below 50% of the baseline values, whereas this did not occur when using the low dose of xylazine in combination with acepromazine. Intravenous acepromazine alone (0.05 mg/kg bwt) did not produce sedative effects (no reductions in HHAG), confirming the results of Lizarraga et al [12]; higher doses (0.1 mg/kg bwt, i.v.) resulted in tranquilisation and mild sedation (SS values of 1 and slight but significant decreases in HHAG) [10,13,14].…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Donkeys receiving the higher dose of xylazine showed HHAG values below 50% of the baseline values, whereas this did not occur when using the low dose of xylazine in combination with acepromazine. Intravenous acepromazine alone (0.05 mg/kg bwt) did not produce sedative effects (no reductions in HHAG), confirming the results of Lizarraga et al [12]; higher doses (0.1 mg/kg bwt, i.v.) resulted in tranquilisation and mild sedation (SS values of 1 and slight but significant decreases in HHAG) [10,13,14].…”
Section: Discussionsupporting
confidence: 84%
“…acepromazine dose of 0.05 mg/kg bwt was shown to achieve sedation in one study , a lack of sedation was reported by the same group of investigators in another study . However, those results should be interpreted cautiously as the former study evaluated sedation subjectively , while the latter study evaluated more specific parameters such as HHAG and a simple 4‐point descriptive sedation scale (SS), with scores from 0 (no sedation) to 3 (marked sedation) . Therefore, including an acepromazine treatment at a dose of 0.05 mg/kg bwt was justified in our study to confirm whether this drug results in sedation or not, as well as to determine whether acepromazine may allow the further reduction of xylazine doses to 0.25 mg/kg bwt.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations